Bridging gaps and leveraging opportunities for One Health: Feedback from the 8th World One Health Congress - Caron, Alexandre; Garine-Wichatitsky, M. de; Figuié, M.; Meunier, J.; Mugabe, P.; Zinsstag, J. (CAB International, 2025)
We attended the 8th WOHC between the 20th and 23rd of September 2024 in Cape Town, South Africa and we provide here our feedback with a specific perspective on the policy implications. The One Health approach still needs to go beyond diseases and to embrace a truly holistic definition of health in both its pathogenic and salutogenic components. This broader definition of health should be applied to all human groups with more equity and inclusivity, to non-human animals, as sentient beings, and to ecosystems and the environment in a more integrated way.